SIMULASI NUMERIK ALIRAN FLUIDA DALAM PENSTOCK DENGAN MENGGUNAKAN COMPUTATIONAL FLUID DYNAMICS (CFD) - Gilang Ramadhan Supit; Hengky Luntungan; Benny L Maluegha (JURNAL POROS TEKNIK MESIN UNSRAT, 2014)
Indonesia has a potential water power resources that can be generated into electricity through hydro power plant (PLTA) and micro hydro power plant (PLTM). The water from the reservoir flow down to the turbine in a penstock, therefore the analysis of the characteristics of the fluid flow in penstock is interesting. This research worked out with a simulation to find the characteristics of fluid flow in the penstock using Computational Fluid Dynamics (CFD) by applying software GAMBIT 2.3.16 and Fluent 6.3.26. Penstock dimension was using the data available and was simulating to find out the characteristics of the flow. The dominant fluid flow characteristics are static pressure, dynamic pressure, total pressure, fluid velocity and shear stress. Result show that for static pressure in inlet 305.769,9 Pa, default-interior 305.769,9 Pa, wall 305,769,9 Pa and outlet 300.009,8 Pa. The dynamic pressure in inlet 3.595,365 Pa, default-interior 4.253,647 Pa, wall 3.602,503 Pa and outlet 4.229,900 Pa. The total pressure in inlet 309.365,3 Pa, default-interior 309.365,3 Pa, wall 309.365,3 Pa and outlet 304.235,4 Pa. The velocity of fluid in inlet 2,681554 m/second, default-interior 2,916727 m/second, wall 2,684047 m/second and outlet 2,908574 m/second. The shear stress in inlet 5,175604 Pa, default-interior 9,589236 Pa, wall 9,589236 Pa and outlet 9,518271 Pa. Keywords: Penstock, Computational Fluid Dynamics (CFD), Fluid Flow Characteristics